Diálogo entre a arquitectura e a pedagogia. Reorganização espaço-funcional como estratégia na procura de uma nova identidade para o espaço escolar - Jéssica Fernandes Costa (2020)
The present work has its origins in the investigation of the various points of contact between the spheres of architecture and pedagogy. It's identified the sense of opportunity of school architecture to establish a dialogue with pedagogy, considering that both intervene and are closely related in the construction of the didactic space. In this sense, it's analyzed, in particular, contemporary rehabilitation interventions in the Portuguese schools, within the scope of the Programa de Modernização do Parque Escolar destinado ao Ensino Secundário. A path is structured aiming to understand and identify the factors that ensure and enhance a new built school environment, committed to the recent pedagogical and sociocultural requirements. The school institution represents a reference as an entity involved in human development. Indeed, school spaces integrate the first memories of space outside the sphere of the home, leading the experiences of personal and interpersonal discovery, which mark the journey from childhood to adult life. In parallel, the contemporary school aims to reflect the human condition of the generation it serves, undertaking a process of disseminating a renewed learning environment, which is assumed to be disconnected from time and place. It is thus reflected in the responsibility of architecture to enhance, through the space-functional reorganization strategy, a new identity for the school space.